A Constructive Criticism on Turnover Taxes - Pistone, Pasquale (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
This chapter focuses on the international implications arising in connection with the uncoordinated exercise of taxing sovereignty by states. It uses the case of sectoral turnover taxes in Hungary and Poland to put forward the merits of coordination with income taxation and the international obligations that countries contract when signing international treaties in tax matters. The chapter acknowledges the growing popularity of those taxes, taking into account their valid policy rationale and their visible implications in the collection of revenue. However, it also stresses the undesirable repercussions arising from the lack of coordination at the international level. All these elements are meaningful components of a comprehensive reform of the international tax nexus, which should not lead each country to pursue just the maximisation of its tax revenue, but also and especially fairness in the allocation of taxing rights at the global level. The author includes arguments drawn from national constitutions and EU law, which support the need for developing this conceptual framework for the exercise of taxing sovereignty in the years to come.